PELATIHAN REBRANDING DAN DIGITALISASI MARKETING BERBASIS WEBSITE PADA UMKM NYI LEHA BATIK - akh fawaid akh fawaid; Masdukil Makruf; Lutfiyanto Lutfiyanto (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Introduction The problem faced by 'Nyi Leha Batik' MSMEs is that product branding is still low. With its main product batik, MSME 'Nyi Leha Batik' is trying hard to compete with almost similar products on the market. Including marketing access too, is one of the problems faced by 'Nyi Leha Batik' MSMEs. Purpose In order to be able to compete with other products, 'Nyi Leha Batik' MSMEs must move up in class. Convenience.Method The method used is carrying out website-based rebranding and digital marketing training.Results The results of this activity include increasing knowledge of 'Nyi Leha Batik' MSME managers regarding rebranding and website-based digital marketing..Recommendationgovernment and private participation so that micro and small businesses can continue to develop. Furthermore, easy access to funding is very necessary for the development of micro and small businesses